Bovine Tuberculosis: The Emergence of a New Wildlife Maintenance Host in Ireland - Kelly, David J.; Mullen, Enda; Good, Margaret (Frontiers in Veterinary Science, 2021)
Despite advances in herd management, tuberculosis (TB) continues to affect ~0.5% of Ireland’s national cattle herd annually. It is clear that any ‘final’ eradication of TB in cattle will need to address all TB maintenance hosts in the same environment. In Ireland and the UK, European Badgers (Meles meles) are a known TB maintenance host, while deer are recognised as spillover hosts. However, deer have been identified as maintenance hosts in other countries and Sika deer, specifically, have been identified with TB in Ireland. We examined the power of cattle, badger and Sika deer densities (at the county level) to predict cattle TB-breakdowns in Ireland, at both the herd and the individual level, using data collected between 2000 and 2018. Our hypothesis was that any positive correlations between deer density and cattle TB-breakdowns would implicate deer as TB maintenance hosts. Using linear multiple regressions, we found positive correlations between deer density and cattle TB-breakdowns at both the herd and individual levels. Since Sika deer in County Wicklow are known to have TB, we ran further regressions against subsets of data which excluded individual Irish counties. Analyses excluding Wicklow data showed much weaker correlations between Sika deer density and cattle TB-breakdowns at both the herd and individual levels, suggesting that these correlations are strongest in County Wicklow. A similar effect for badger density was seen in County Leitrim. While locally high densities of Sika deer persist in Irish counties, we believe they should be considered an integral part of any TB-control programme for those areas.